Characteristics of Graphene Like Material Synthesized from Coconut Shell Charcoal Powder using Solid State Method - Baiq Lisna Najati; Norman Syakir, Fitrilawati (Universitas Padjadjaran, 2023)
We synthesized graphene like material from coconut shell charcoal powder (CSP) using solid-state method followed by exfoliation using H2SO4. In the synthesis, CSP was mixed with KOH in a ratio of 1:5 followed by heating at a temperature of 850ºC for 1 hour to obtain Coconut Shell Graphitization (CSG). The synthesized CSG was then exfoliated for 1 hour using ultrasonication in H2SO4 which was referred as Coconut Shell Graphitization_Exfoliated (CSG_E). The infrared spectra results of the two products showed the presence of C-C, C=C, C-O-C, C-O-OH groups which are characteristics of reduced graphene oxide (rGO). The Raman spectroscopy results show that the synthesized materials have D and G bands with ID/IG ratio of 0.98-0.96, that indicates the presence of impurities in the form of an oxide group on the graphene surface. Decomposition analysis using the help of the Lorentz Function show that the XRD pattern of the synthesized material have graphene structure at 2θ = 26.59º, and the rGO structure at 13.88º, and 19.09º with its 2nd order at 42.89º. The measurement results indicate that the synthesized materials are rGO. The data analysis shows that CSG consists of 83.09% rGO and 16.91% graphene, after exfoliation the rGO content of CSG_E rises to 87.27%